EVALUASI PROGRAM DIKLAT PRAJABATAN GOLONGAN III - JUANDA JUANDA (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2011)
The objective of this research is to explore the effectiveness of the third level civil servant pre-service training. This research was conducted at Balai Diklat Keagamaan Jakarta, involving 800 pre-service teachers of MORA’s school. This research uses Kirkpatrick’s model of evaluation. The research presented four conclusions. Firstly, only 43% of the instructors’ performances are good. Secondly 64% of the materials are not correlative with the participants’ requirements. Thirdly, the equipments of the training are good rate. The fourth, the goal of the training as to improve the participants’ knowledge and skill that related to their job are very low (36%), but attitudes changed due to the training are good (60%).